PELATIHAN AKUNTANSI BERBASIS TEKNOLOGI SEBAGAI PEMBEKALAN MENGHADAPI DUNIA KERJA PADA SMK METHODIST TANJUNG MORAWA - Tarihoran, Anita; Riny, Riny; Tarigan, Purnaya Sari; Loman, Devina (Jurnal Pengabdian Bukit Pengharapan, 2023)
Rapid technological developments require companies to be able to adapt and use technology to achieve effective and efficient results. The use of the latest technology is expected to improve the company's business prospects. One of the things to be achieved is the timely availability of information in financial reports. To support this, businesses or companies take advantage of the flexibility, features and process automation of accounting software. However, not many schools have introduced or included learning about accounting software into the curriculum. Accurate Software is accounting software that helps to record bookkeeping and makes it easier to manage financial data with the right level of calculation accuracy. SMK Methodist Tanjung Morawa is one of the educational units with a vocational school level which is expected to be ready to enter the labor market so that it is directly equipped with the vocational knowledge needed. Currently, they still use and record accounting manually in their learning process and until now there has been no introduction and use of accounting-based software. The aim of this training is to provide new skills in using accounting applications, namely the Accurate application, which supports their understanding while at school. This activity will be carried out for SMK Methodist Tanjung Morawa.